Kontruksi Madzhab Hadis Mu’tazilah (Studi Analisis aliran Mu’tazilah dalam memahami Hadis) - Muhammad Alfreda Daib Insan Labib; Ahmad Muchlis (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
This article discusses how the mu'tazilah school understands hadith. As a group that understands the source of religion by prioritizing ratios, of course there are differences with other groups. This study consists of the understanding of the mu'tazilah and the history of their emergence, the main teachings of the mu'tazilah and their figures, the mu'tazilah during the time of the Ummayah and Abbasiyah, the discourse on the blasphemy of the hadith ahad, the history of its denial, and the hadith ahad in the mu'tazilah review. This study method is descriptive analysis, which describes the data that has been collected then processes it and analyzes related data. The results of this study are 1). The mu'tazilah had a different approach to the Sunnah. 2). mu'tazilah have certain principles, which if the hadith of the Prophet contradicts those principles, they reject them. 3). Reason occupies the top position in understanding the evidence of the Shari'a.